Transisi Pengelolaan Pajak Bumi dan Bangunan Perdesaan Dan Perkotaan Di Kabupaten Sleman - Sarwana, Tamzis; Mutiarin, Dyah (Universitas Muhammadiyah Yogyakarta, 2014)
Strengthen central government’s financial policy areas mor e pronounced with enactment of Law No.28/2009 onLocal Taxes and Levies which authorizes 11 types of local taxes, including authority to manage land and building taxRural and Urban (PBB-P2). The study was conducted in Sleman regency government to know pendaerahan process,transition and implementation as well as the picture before and after the transition of the management PBB-P2 years2009-2013. Descriptive and qualitative research methods, data collection techniques with interviews, documentation,and questionnaires. Qualitative descriptive data analysis techniques and interactive data analysis. Conclusion research1. Tax Pendaerahan under Law No.28/2009 implemented by the authority manages the collection of 10 of the 11types of taxes for 2-6 years on average above 100%. 2. Transition PBB-P2 management optimal implemented by theRegional Regulation and drafting the decree, the formation of Receipt, preparation and improvement of human re-sources, the availability of budget, equipment, data, and the establishment of partnerships. 3. Implementation ofPBB-P2 management authority in the transition to establishment of technical regulations, administration, and man-agement system PBB-P2. 4. Picture before and after the transition of the PBB-P2 management in Sleman regencygovernment showed its management work well. Researchers suggestion is to expand co-operation, maintenance andrenewal of the United Nations data bases PBB-P2, increased capacity and welfare of the United Nations managersPBB-P2.